Pollen assemblage and environmental DNA changes: A 4300-year-old bat guano deposit from Jamaica. (30th August 2020) - Bogdanowicz, W.; Worobiec, Elżbieta; Grooms, C.; Kimpe, L.E.; Smol, J.P.; Stewart, R.S.; Suchecka, E.; Pomorski, J.J.; Blais, J.M.; Clare, E.L.; Fenton, M.B.
Abstract: The discovery of two undisturbed caves in Jamaica with 14 C and 210 Pb dating indicating that the oldest layers of guano were ca. 200 years old in the first cave (81 cm long core), and as much as 4300 years old in the second cave (129 cm long core) provides exciting possibilities to examine past ecological communities. We analyzed genetic and pollen profiles in these ancient bat guano deposits and revealed DNA sequences most similar to arthropods, mainly insects such as caddisflies (Trichoptera), butterflies (Lepidoptera) and mayflies (Ephemeroptera), suggesting a potential source for past dietary data. Palynological analysis failed to recover well-preserved pollen grains and spores older than ca. 200 years, however in layers preserving pollen, angiosperms were the most abundant plants observed, with a regular occurrence of the potato (Solanaceae) and pepper families (Piperaceae), which are frequently bat-dispersed. In general, changes in frequency of particular plant taxa appear to reflect changes of vegetation and land use in the cave vicinity; however, some changes could be linked to hurricanes, leading to forest canopy damage and promoting the growth of light-demanding species such as guarumo ( Cecropia ). Higher amounts of mangrove ( Rhizophora ) pollen have also been recorded in the periods of heavy hurricane activities. Our data highlight the value of bat guano deposits in caves as a resource for the analysis of past ecological systems and stress the conservation values of these deposits.